2006
DOI: 10.1002/elan.200603619
|View full text |Cite
|
Sign up to set email alerts
|

Amperometric Detection of H2O2 Using Gold Electrodes Modified with Starburst PAMAM Dendrimers and Prussian Blue

Abstract: Gold-bead electrodes were modified by covalent bonding or physical adsorption of several Starburst PAMAM dendrimers (generations 2.0, 3.0 and 4.0) followed by absorption of Prussian Blue (PB). The covalent dendrimer-PBmodified electrodes can be used as amperometric sensors of H 2 O 2 in aqueous solution. They offer enhanced sensitivity with correspondingly lower detection and quantification limits compared to similar amperometric detectors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Hydrogen Peroxide (9) The reduction of hydrogen peroxide is catalysed by PB (K 2 Fe 4 III [Fe II (CN) 6 ] 3 •14H 2 O) through the mediation of the ferric ions by electron transfer to H 2 O 2 molecules from Fe 2+ centers in the PB, with the next electrochemical reaction (19):…”
Section: Discussion Of Resultsmentioning
confidence: 99%
“…Hydrogen Peroxide (9) The reduction of hydrogen peroxide is catalysed by PB (K 2 Fe 4 III [Fe II (CN) 6 ] 3 •14H 2 O) through the mediation of the ferric ions by electron transfer to H 2 O 2 molecules from Fe 2+ centers in the PB, with the next electrochemical reaction (19):…”
Section: Discussion Of Resultsmentioning
confidence: 99%
“…A lot of quantitative methods have already been applied for the detection of H 2 O 2 , most of them are based on spectrometry [ 42 45 ], chemoluminescence [ 46 49 ], amperometry [ 50 53 ] and electrochemistry [ 54 57 ]. The conventional spectrometric and chemoluminescence methods are commonly time-consuming and costly.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shown that electrodes modified with metal and oxide nanoparticles, such as Pt [8,9] , Au [10] , MnO 2 [11,12] , Fe 3 O 4 [13] , Ag [14][15][16][17][18] , and CuO [19,20] nanoparticles, exhibit good catalytic activity for H 2 O 2 . H 2 O 2 sensors based on nanomaterial electrodes are growing continuously [21][22][23] . Palladium (Pd) nanoparticles with high hydrogen storage capability and remarkable electrocatalytic activities toward various important substrates have gained increasing research interests [24][25][26][27] .…”
Section: Introductionmentioning
confidence: 99%